2011
DOI: 10.1111/j.1365-2966.2011.18423.x
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse intracluster light at intermediate redshifts: intracluster light observations in an X-ray cluster at z= 0.29★

Abstract: The diffuse intracluster light (ICL) contains a significant fraction of the total stellar mass in clusters of galaxies, and contributes in roughly equal proportion as the hot intracluster medium to the total baryon content of clusters. Because of the potential importance of understanding the origin of the ICL in the context of the formation and evolution of structure in the Universe, the field has recently undergone a revival both in the quality and quantity of observational and theoretical investigations. Bec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 28 publications
6
40
1
Order By: Relevance
“…On the other hand, other studies report super-solar metallicities in the diffuse light in Abell 3888 (1.0 Z < Z < 2.5 Z , Krick et al 2006) that are interpreted as ICL formed early with the collapse of the main cluster, unrelated to the BCG halos. From a kinematic point of view, the line-of-sight velocity distribution of intra-cluster planetary nebulae in one Coma cluster core field is consistent with the ICL being formed from stars stripped from the halos of the two brightest galaxy in the cluster while they orbit each other , while recent studies of absorption line spectra in the RX J0054.0-2823 cluster are consistent with the ICL being the remnant of tidally destroyed galaxies and streaming in the central regions of the cluster, in which the three central giant ellipticals act as "grinding machines" (Toledo et al 2011). The origin of the ICL and its connection with the BCG halos is thus not fully understood, and it is likely that several mechanisms are acting in its formation.…”
Section: Introductionmentioning
confidence: 58%
“…On the other hand, other studies report super-solar metallicities in the diffuse light in Abell 3888 (1.0 Z < Z < 2.5 Z , Krick et al 2006) that are interpreted as ICL formed early with the collapse of the main cluster, unrelated to the BCG halos. From a kinematic point of view, the line-of-sight velocity distribution of intra-cluster planetary nebulae in one Coma cluster core field is consistent with the ICL being formed from stars stripped from the halos of the two brightest galaxy in the cluster while they orbit each other , while recent studies of absorption line spectra in the RX J0054.0-2823 cluster are consistent with the ICL being the remnant of tidally destroyed galaxies and streaming in the central regions of the cluster, in which the three central giant ellipticals act as "grinding machines" (Toledo et al 2011). The origin of the ICL and its connection with the BCG halos is thus not fully understood, and it is likely that several mechanisms are acting in its formation.…”
Section: Introductionmentioning
confidence: 58%
“…Similarly, using various samples, Feldmeier et al (), Zibetti et al () and Krick et al () conclude between them that contamination by non‐cluster galaxies is not significant out to z ≃ 0.3. A more robust approach is taken by Toledo et al (), who account for non‐member contamination by calculating the luminosity function of the cluster from spectroscopically confirmed members and then integrating the fitted luminosity function out to faint magnitudes to find the total luminosity of the cluster.…”
Section: Resultsmentioning
confidence: 99%
“…For example, as mentioned in Section , Gonzalez et al (, ) fit the surface brightness profile of the BCG using two DeVaucouleurs profiles. A similar method was followed by Toledo et al (), where all the galaxies in the cluster were masked out except for the BCG, and the surface brightness profile of the extended BCG component was measured. This kind of measurement naturally provides estimates of the fraction of cluster light which is contained in the BCG+ICL.…”
Section: Measuring the Iclmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in Section 7, Gonzalez et al (2007) posit that the relevant quantity is f IHL+BHG , because it can be difficult to disentangle the stellar mass associated with the central galaxy from the diffuse IHL component. It has been found that f IHL+BHG ∼ 30% on average on cluster scales (Zibetti et al 2005;Gonzalez et al 2007;Pierini et al 2008;Toledo et al 2011).…”
Section: Summary and Discussionmentioning
confidence: 99%